2004
DOI: 10.3406/aru.2004.2566
|View full text |Cite
|
Sign up to set email alerts
|

Quand les villes font appel aux religions : Laïcité et nouvelles prises en compte de la pluralité religieuse

Abstract: When Cities call on Religions Over the last two decades, some mayors of large French cities have taken the initiative of organizing meetings between churches of different denominations. In Marseilles, Roubaix or Montreuil, information and exchange systems are becoming established on a long-term basis and take various legal forms. Certain world or local events give momentum to these interdenominational encounters, at the risk of causing a confusion between religious and social or ethnic reality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…In particular, the development of the "super-diversity" approach associated with Steve Vertovec (2007, see also , Gidley 2019 highlights the diversification of differences -the proliferation of, and interactions between, lines of nationality, 'race' and ethnicity, faith and class, among other axes -and points towards power geometries and inequalities within as well as between apparent groups. This approach allows us to see faith alongside race as a determining but still contingent and intersectional dimension of social fates, and Lamine (2004) has shown that, even in avowedly secular France, municipal actors have begun to embrace a diversity paradigm in engaging with religious minorities.…”
Section: Alternative Frames and Ambivalent Encountersmentioning
confidence: 99%
“…In particular, the development of the "super-diversity" approach associated with Steve Vertovec (2007, see also , Gidley 2019 highlights the diversification of differences -the proliferation of, and interactions between, lines of nationality, 'race' and ethnicity, faith and class, among other axes -and points towards power geometries and inequalities within as well as between apparent groups. This approach allows us to see faith alongside race as a determining but still contingent and intersectional dimension of social fates, and Lamine (2004) has shown that, even in avowedly secular France, municipal actors have begun to embrace a diversity paradigm in engaging with religious minorities.…”
Section: Alternative Frames and Ambivalent Encountersmentioning
confidence: 99%
“…In parallel, there is a trend towards promoting mechanisms of deliberative and participatory democracy, which municipal authorities use, among other things, to improve management and fight communautarisme (Jouve 2005). 2 Despite France's legal separation of church and state, participatory devices have also spread in the field of religion, and religious actors are increasingly conceived as governance partners because they provide urban political authorities with important resources (De Galembert 2006;Lamine 2004b). The three participatory bodies in this study constitute 'invited spaces' in which the municipality invites different urban actors, including religious actors, to participate.…”
Section: Religion In Consultative Bodies: a Tale Of Three French Citiesmentioning
confidence: 99%
“…« Municipal interreligious dialogue in Bordeaux: between the 'politics of diversity' and a Catholicentric laïcité », Annual Review of the Sociology of Religion n°10 «Interreligious Dialogue: From Religion to stance is in line with the position of Alain Juppé, who refuses to view laïcité as a right-wing idea or as an instrument of discrimination against Muslims in France. Lamine (2004) has suggested that inter-religious dialogue as a contribution to "living together" might be regarded as an ideal-type of "civil religion" congruent with the French model of laïcité. Such a civil religion could indeed enable political leaders to take the religious pluralization of large French cities into account, and to seemingly respect the principle of neutrality by integrating all religious actors on equal terms.…”
Section: A Catholic Footprintmentioning
confidence: 99%